(untitled) (Journal of International Studies, 2017)
The world is undergoing the process of transition ranging from orthodox traditionalist to the modern colonial system of multipolar divergent domination of colonial agenda and later transcending to bipolar twin ideological dominance of western capitalist and easterncentral planned economy with modern technological development. This trend has really transformed the global scenario to enter into modern clutches since Second World War upto the terminal point of the cold war in early 90’s. Meanwhile, the new post-cold war global agenda came up with new changes such as “modern advancement, revolution in information, communication and technology, globalization, liberalization of economy, democracy and democratization process among others. Content analysis was the methodology that the researchers adopted in this paper. The study reveals that globalization and modernity have detrimental impacts on African culture and politics in areas of its political system, economy, education, religion and socio-psychological systems. The paper recommends that Africansshould maintain their culture, norms and values as well as enhance the national boundary and sovereignty so as meet the challenges of globalization.